Industrialised Building System (Ibs) Scoring System - Case Study - Ibrahim, Siti Rus‘Adneen (Universiti Sains Malaysia, 2006)
The Malaysian construction in industry is undergoing a transitional change from an industry employing conventional technology more to systematic and mechanized system. This new system known as the Industrialised Building System.